2013
DOI: 10.1139/cjz-2012-0155
|View full text |Cite
|
Sign up to set email alerts
|

Stable isotope turnover and variability in tail hairs of captive and free-ranging African elephants (Loxodonta africana) reveal dietary niche differences within populations

Abstract: Many herbivore species expand their dietary niche breadths by switching from browse-rich diets in dry seasons to grass-rich diets in rainy seasons, in response to phenological changes in plant availability and quality.Weanalyzed stable isotope series along tail hairs of captive and free-ranging African elephant (Loxodonta africana (Blumenbach, 1797)) to compare patterns of seasonal dietary variability across individuals. Results from elephants translocated from the wild into captivity, where their diets are se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 55 publications
0
13
0
Order By: Relevance
“…Finally, in order to estimate the level of variability across individuals, we used the average of all Euclidean distances (ED) between individual pairs. This approach differs from previous efforts using longitudinal data for individuals (e.g., Newsome et al, 2009;Vander Zanden et al, 2010;Codron et al, 2012bCodron et al, , 2013aRobertson et al, 2014). We demonstrate here how insights into individual-level differences can be drawn in the absence of such temporal series, and discuss the advantages and drawbacks below.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Finally, in order to estimate the level of variability across individuals, we used the average of all Euclidean distances (ED) between individual pairs. This approach differs from previous efforts using longitudinal data for individuals (e.g., Newsome et al, 2009;Vander Zanden et al, 2010;Codron et al, 2012bCodron et al, , 2013aRobertson et al, 2014). We demonstrate here how insights into individual-level differences can be drawn in the absence of such temporal series, and discuss the advantages and drawbacks below.…”
Section: Discussionmentioning
confidence: 89%
“…The small sample of longer-term carbon isotope profiles presented in Figure 6 supports our conclusions, but is too small to be considered a thorough test of all hypotheses raised here. Similarly, published isotopic time series for individual African elephants (Codron et al, 2012b(Codron et al, , 2013a, forest hogs (Hylochoerus meinertzhageni; n = 3; Cerling and Viehl, 2004), oryx (Oryx gazelle), and springbok (Lehmann et al, 2013(Lehmann et al, , 2015 have revealed much higher levels of withinthan between-individual isotope niche variability amongst herbivores. Nevertheless, until more longitudinal records of isotopic variability for a wider variety of species of both carnivores and herbivores are available, we can only conclude that overall isotopic niche variability, and the opportunity for individual specialization, is higher for carnivores than it is for herbivores.…”
Section: Discussionmentioning
confidence: 94%
“…In recent years, segmental stable isotope analysis of hair has been a research focus of animal dietary ecology and migration. [1][2][3][4][5][6][7] The isotope abundance of 2 H and 18 O in animal tissue (including hair) provides information on water intake, which is a reflection of the geographical location, and the isotope abundance of 13 C and 15 N provides information on diet and nutritional status. [8,9] Tail hair is an ideal matrix for stable isotope analysis because it grows continuously in many species and is isotopically inert after formation.…”
mentioning
confidence: 99%
“…One potential influence at the community level is that more small- to medium-sized prey must have been available to dinosaurian than mammal carnivores. Also, dinosaurs would have experienced more ecological niche shifts through life, as occurs during ontogeny in many species both oviparous and viviparous [70][74]. Since similar-sized individuals of a given trophic level often share a similar niche space, the relatively high niche diversity within dinosaur species surely meant more overlaps - and hence more frequent competitive interactions - across species.…”
Section: Discussionmentioning
confidence: 99%